Synthesis and Structural Characterization of Fly Ash Based Mineral Polymer Precursors - Miao, Xia; Yimiao, Nie; Shuxian, Liu; Ling, Wang; Long, Wang; Sen, Wang (Frontiers in Materials, 2022)
Preparation of mineral polymer materials with fly ash is one of the effective ways to realize the green comprehensive utilization of fly ash. Using sol-gel method mineral aggregate material precursor, studied the different source of silicon and aluminum source, synthesis temperature, different Si/Al ratio, different dosage of ethanol and other influence factors under the conditions of the synthesis, the structure of the sample using the means of XRD, SEM, TG, IR on the synthesis of silica alumina precursor sample performance and structure are analyzed. The results showed that the optimum preparation conditions were obtained when the Si/Al ratio was 10:1, the synthesis temperature was 70℃, and the sample was calcined at 850℃ for 3h with the highest synthesis rate of 81.33%. The Si-Al precursors prepared are amorphous - phase amorphous grid - space structures. The infrared analysis indicated that the synthesized sample had Si-O-Si bond, but the absorption peak and characteristic peak were obviously different under the conditions of different synthesis temperature, different Si/Al ratio and different ethanol dosage. For example, at 806cm-1 and 1395cm-1, they correspond to the absorption peak of Si-OH bending vibration and shear bending vibration and plane bending vibration of C-H without complete reaction respectively. SEM observation shows that the size of the synthesized Silicon aluminum precursors sample is small and the distribution is uniform. With the in-depth study on the preparation process and reaction mechanism of mineral polymer precursors, it will bring broad prospects for the application and development of mineral polymer precursors themselves.